Speech synthesis by phonological structure matching. - Taylor, Paul; Black, Alan W (International Speech Communication Association, 1999)
This paper presents a new technique for speech synthesis by unit selection. The technique works by specifying the synthesis target and the speech database as phonological trees, and using a selection algorithm which finds the largest parts of trees in the database which match parts of the target tree. The technique avoids many of the errors made by prosody generation modules by incorporating their operation in the selection implicitly. A technique for using signal processing only when it is needed most is also described. The technique produces better quality speech than previous approaches and is also significantly faster.